„Die unterschiedlichen Perspektiven, die unterschiedlichen Grundvoraussetzungen (…), die unterschiedliche Sprache“ – Prozesse interorganisationaler Zusammenarbeit im Kontext des InnoVET-Programms - Breuing, Friederike

VET innovation projects in Germany – Overview of and insights into a qualitative study on processes of inter-organisational cooperation - Breuing, Friederike

HR-Praktiken als Ressourcenmanager: Wie die Schwächen flexibler und unflexibler Arbeitsmodelle kompensiert werden können. Studie Industrieverband Büro und Arbeitswelt e.V.. - Radermacher, Katharina; Schneider, Martin

Innovationsprojekte in der beruflichen Bildung – Studie zu Prozessen interorganisationaler Zusammenarbeit im Kontext des InnoVET-Programms - Breuing, Friederike

Are firms (getting) ready for the corporate sustainability reporting directive? - Kosi, Urska; Relard, Paula (Sustainability Nexus Forum)
The study examines whether the announcement and passing of the Corporate Sustainability Reporting Directive (CSRD) impacts the sustainability reporting of German firms. It sheds light on the interdependence of various actors, sectors and policy levels by examining how regulatory changes at the policy level affect the reporting practices of firms across multiple sectors. On the one hand, the scope of the CSRD is being extended, so that new firms falling within its scope may increase their voluntary sustainability reporting as part of the preparation process. On the other hand, the reporting requirements will be more stringent, so that firms currently under the mandate of the Non-Financial Reporting Directive (NFRD) may enhance their sustainability reporting disclosure practices in preparation for the CSRD. First, we find no increase in voluntary sustainability reporting by firms that are not under the scope of the NFRD but will be under the scope of the CSRD. Second, we find enhanced sustainability reporting practices by firms that are subject to the NFRD after the CSRD’s announcement and passing. This finding suggests that these firms begin to implement the new reporting requirements before the first reports are published in 2025. We illuminate the preparation for extensive reporting changes through sustainability reporting disclosure practices as an outcome of the preparation process. These changes may represent a high burden, particularly for firms with no previous experience of sustainability reporting.

Eine Analyse der Arbeitsplatzkonzepte preisgekrönter Unternehmen. Auf dem Weg zum Arbeitsplatz der Zukunft. - Radermacher, Katharina; Rösener, M.

Understanding cognitive decline in older ages: The role of health shocks - Schiele, Valentin; Schmitz, Hendrik (European Economic Review)
Individual cognitive functioning declines over time. We seek to understand how adverse physical health shocks in older ages contribute to this development. By use of event-study methods and data from the USA, England, and several countries in Continental Europe, we find evidence that health shocks lead to an immediate and persistent decline in cognitive functioning. This robust finding holds in all regions representing different health insurance systems and seems to be independent of underlying individual demographic characteristics such as sex and age. We also ask whether variables that are susceptible to policy action can reduce the negative consequences of a health shock. Our results suggest that neither compulsory education nor retirement regulations moderate the effects, thus emphasizing the importance for cognitive functioning of maintaining good physical health in old age.

The Role of Response Time for Algorithm Aversion in Fast and Slow Thinking Tasks - Lebedeva, Anastasia; Kornowicz, Jaroslaw; Lammert, Olesja; Papenkordt, Jörg (Artificial Intelligence in HCI)

Are Numbers or Words the Key to User Reliance on AI? - Papenkordt, Jörg; Ngonga-Ngomo, Axel-Cyrille; Thommes, Kirsten (Academy of Management Proceedings)

Employer Branding - Wie Arbeitgeber strategisch gegen den Arbeitskräftemangel vorgehen. - Schneider, Martin; Radermacher, Katharina (Die Politische Meinung)

A model of cycles and bubbles under heterogeneous beliefs in financial markets - Burs, Carina (Cogent Economics & Finance)
I study the effect of heterogeneous beliefs about asset prices on the long-term behavior of financial markets. Starting from the ideas of Abreu and Brunnermeier (Citation2003), a two-dimensional system of differential equations is developed. The first dynamic variable is the asset price growth rate. The second dynamic variable is the number of investors who believe that asset prices are abnormally high. In a phase plane analysis, I find both stable and unstable equilibria, depending on the spread of information and the response to other agents’ beliefs. If individuals try to increase their returns while perceiving more overpricing, these equilibria can be spirals or even approach limit cycles. Although I intend to study general price patterns, abnormally high asset prices can be caused by financial bubbles. In this model, bubbles can emerge and deflate both in cycles or directly, or they can grow until they burst. Further, I analyze market behavior after a central bank increases the interest rate. This can lead to new stable equilibria, but the emergence and bursting of bubbles cannot be prevented.
Keywords: asset pricing; subjective information; stability conditions; monetary policy; risk aversion

Frühe Versuche zur Etablierung des Hochschulstandorts Paderborn (1945-1970) - Grüttner, Niclas Christian (50 Jahre Universität Paderborn. Studentische Forschungsprojekte zur Gründungsgeschichte. Ein Rückblick)

The Choice of Ideology and Everyday Decisions - Burs, Carina; Gries, Thomas; Müller, Veronika (Journal of Organizational Psychology)
Individuals strive to make decisions that are consistent with not only their consumer preferences but also their psychological needs. However, they are confronted with complex, ambiguous or even false information. Ideologies and belief systems provide guidance when processing and evaluating information and give a coherent and comprehensible interpretation of reality. The first question is: why is an individual attracted to a particular ideology? Individuals choose ideologies that resonate with their subjective psychological needs and preferences. Second, how do individuals search for ideologies and find out which suit them best? We model an individual’s sequential information search for the best matching ideologies by applying Bayesian learning and utility optimization. Additional information enhances utility by reducing uncertainty. As a search is costly, the process may stop once an individual adopts an ideology even if the information set remains incomplete. Third, once they have chosen a particular ideology, individuals adhere to its rules and norms when making everyday decisions. Consumers not only physically consume, but they also act in accordance with their psychological needs.
Keywords: Economics; Ideology; Decision-making

Erlebnisorientiert Lehren und Lernen in der beruflichen Bildung. Entwicklung eines didaktischen Konzepts im Rahmen von designbasierter Forschung. - Volgmann, Simone

An IAD framework analysis of minigrid institutions for sustainable rural electrification in East Africa: A comparative study of Uganda and Tanzania - Namujju, Lillian Donna; Acquah-Swanzy, Henrietta; Ngoti, Irene F. (Energy Policy)
Keywords: Management; Monitoring; Policy and Law; General Energy

Frühe Versuche zur Etablierung des Hochschulstandorts Paderborn (1945-1970) - Grüttner, Niclas Christian (50 Jahre Universität Paderborn. Studentische Forschungsprojekte zur Gründungsgeschichte. Ein Rückblick)

Reviewing from a Distance: Uncovering Asymmetric Moderations of Spatial and Temporal Distances Between Sentiment Negativity and Rating - Neumann, Jürgen; Gutt, Dominik; Kundisch, Dennis (MIS Quarterly)

Collective Minimum Contributions to Counteract the Ratchet Effect in the Voluntary Provision of Public Goods - Alt, Marius; Kesternich, Martin; Gallier, Carlo; Sturm, Bodo (Journal of Environmental Economics and Management)
We experimentally test a theoretically promising amendment to the ratchet-up mechanism of the Paris Agreement. The ratchet-up mechanism prescribes that parties’ commitments to the global response to climate change cannot decrease over time, and our results show that its effect is detrimental. We design a public goods game to study whether cooperation is promoted by an amendment to the mechanism that stipulates that all agents must contribute at least a collectively chosen minimum based on the principle of the lowest common denominator. We find that binding collective minimum contributions improve the effectiveness of the ratchet-up mechanism. Non-binding minimum contributions, by contrast, do not encourage cooperation. Our data indicate that the difference is attributable to conditional cooperative dynamics. If other participants contribute less than the collective minimum contribution, even initially cooperative participants start to negatively reciprocate this form of non-compliance by contributing less.
Keywords: global public goods; climate change; institutions; ratchet-up mechanism; minimum contributions; laboratory experiment

Role (in-)congruity and the Catch 22 for female executives: how stereotyping contributes to the gender pay gap at top executive level - Diederich, Sarah; Iseke, Anja; Pull, Kerstin; Schneider, Martin (The International Journal of Human Resource Management)
Keywords: Management of Technology and Innovation; Organizational Behavior and Human Resource Management; Strategy and Management; Business and International Management; Industrial relations

Inter-Charity Competition under Spatial Differentiation: Sorting, Crowding, and Spillovers - Gallier, Carlo; Goeschl, Timo; Kesternich, Martin; Lohse, Johannes; Reif, Christiane; Römer, Daniel (Journal of Economic Behavior and Organization)